2002
DOI: 10.1088/0953-2048/15/11/316
|View full text |Cite
|
Sign up to set email alerts
|

Reversible melting and equilibrium phase formation of (Bi, Pb)2Sr2Ca2Cu3O10  

Abstract: The decomposition and the re-formation of the (Bi, Pb)2Sr2Ca2Cu3O10+δ (Bi, Pb(2223)) phase have been investigated in situ by means of high-temperature neutron diffraction, both in sintered bulk samples and in Ag-sheathed monofilamentary tapes. Several decomposition experiments were performed at various temperatures and under various annealing atmospheres, under flowing gas as well as in sealed tubes, in order to study the appropriate conditions for Bi,Pb(2223) formation from the melt. The Bi,Pb(2223) phase was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…In spite of this success, this technique has not been used to prepare tapes or multifilament materials at an industrial scale because it was thought that any melting would decompose the Bi 2223 phase and a long period of annealing at a lower temperature would be necessary to recover this phase; long annealing and even a partial melting of chemical precursors have been used to obtain the Bi 2223 phase. Recently, experiments have again shown that this phase can be rapidly recomposed after melting, in agreement with the previous work on magnetic texturing [30,31]. All these results indicate the existence, above the liquidus temperature, of unmelted crystals acting as crystal growth nuclei.…”
Section: Bi 2223supporting
confidence: 89%
“…In spite of this success, this technique has not been used to prepare tapes or multifilament materials at an industrial scale because it was thought that any melting would decompose the Bi 2223 phase and a long period of annealing at a lower temperature would be necessary to recover this phase; long annealing and even a partial melting of chemical precursors have been used to obtain the Bi 2223 phase. Recently, experiments have again shown that this phase can be rapidly recomposed after melting, in agreement with the previous work on magnetic texturing [30,31]. All these results indicate the existence, above the liquidus temperature, of unmelted crystals acting as crystal growth nuclei.…”
Section: Bi 2223supporting
confidence: 89%
“…The unit-cell parameters were calculated regarding an orthorhombic unit cell and the obtained values a = 5.410 Å, b = 5.413 Å, and c = 37.152 Å are in line with those reported elsewhere for the same compound [15][16][17]. The occurrence of grains with platelet-like structure in Bi-based materials is well known, as reported previously in our samples [9,12].…”
Section: Resultssupporting
confidence: 88%
“…However, intrinsic limits to this route seem to come from the formation mechanisms where the transient liquid assisting the Bi,Pb(2223) formation is not stable and results in a poor structural homogeneity. E. Giannini et al showed that it is possible to form the Bi,Pb(2223) phase from a liquid close to the equilibrium conditions following a reversible melting of the Bi,Pb(2223) phase exactly in the same way as J. Noudem et al did in bulk samples [39]. Then, Bi2223 intrinsic nuclei exist in the melt.…”
Section: Ag-sheated Tapes Of Bi2sr2ca2cu3o8+xmentioning
confidence: 75%